“Poverty of World”. An inquiry into the humanism and the World of life in the frame of Martín Heidegger’s thinking - Candiloro, Hernán J. (Revista de Filosofía, 2015)
In 1929 Heidegger characterizes animality in terms of “poverty of world”. However, some years later he uses the same expression “poverty” to mean the being of the man and the possibility of “realizing” his relation to being in general through the thinking. In this context, our article proposes an inquiry in the meaning of “poverty of world”, to explicit it like an attempt to deconstruct the traditional humanism, by which the man meets again his animality in the context of the world of life.